Operating Guidelines for AMAP Working Group. - Arctic Monitoring and Assessment Programme (AMAP) (Arctic Council Secretariat, 2001)
"The Arctic Monitoring and Assessment Programme (AMAP) is carried out by the AMAP working group (AMAP WG) under the Arctic Council (AC) and as such operates under the Rules of Procedure that exist for the AC. These guidelines should be read in conjunction with the Rules of Procedure of the Arctic Council”." /./